Evaluating the Effect of Bone Morphogenetic Protein on Dental Implant Stability and Marginal Bone Level Following Immediate Implant Placement (Randomized Controlled Clinical Study) - Aya A. Saeed; Ali H. Abbas (Journal of Craniofacial Surgery, 2026)
Background: Immediate implant placement has become a widely accepted treatment modality because of reduced treatment time and preservation of alveolar bone architecture. Recombinant human bone morphogenetic protein-2 (rhBMP-2) has been proposed to enhance peri-implant bone regeneration and implant stability. This study evaluated the effect of recombinant human bone morphogenetic protein-2 (rhBMP-2) combined with biphasic calcium phosphate graft on implant stability and peri-implant bone preservation following immediate implant placement. Methods: Twenty-four patients who received 32 immediate dental implants were randomly assigned to 2 groups. The control group received a biphasic calcium phosphate graft alone in the jumping gap, whereas the study group received the graft combined with 0.1 mg rhBMP-2. Implant stability, marginal bone level, and buccal bone thickness were evaluated clinically and radiographically over 16 weeks. Results: Thirty implants were analyzed. Both groups showed a significant increase in implant stability over 16 weeks. The control group demonstrated a slightly higher relative percentage increase than the study group (11.17%±4.34 versus 9.57%±3.83), with no statistically significant difference between groups ( P =0.637). No statistically significant differences were observed regarding marginal bone loss or buccal bone thickness changes at 1 mm and 2 mm below the implant screw ( P >0.05). Conclusions: The addition of rhBMP-2 to a biphasic calcium phosphate graft did not confer significant clinical advantages over the graft alone following immediate dental implant placement, suggesting limited additional benefit relative to its cost.